Traffic Network Optimal Scheduling Paths Based on Time Intervals Division - Hao Wei; Zhang Xing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to make the network model was more fitting the actual condition of city traffic, this paper presents a dynamic transportation network model based on the traffic time division, and designs improved Dijkstra algorithm to solve the city traffic paths planning problem. Dijkstra algorithm is a typical single-source shortest path algorithm is used to calculate a node to all other nodes in the shortest path. The main characteristic is the starting point as the center outward expansion layers until the extension to the end. The Dijkstra algorithm is a very representative shortest path algorithm. This paper introduces new patterns to effectively combine the model and algorithm. The simulation experiments point to ten time intervals which illustrate the improved Dijkstra algorithm can avoid driving to the blocked roads in different time intervals. The algorithm has some feasibility in path planning and computation efficiency. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4306